Анализ гармонического состава переменного магнитного поля, связанного с вращающимся ротором турбогенератора, в режимах холостого хода и короткого замыкания - Милых, Владимир Иванович; Полякова, Наталия Владимировна; Milykh, V. I.; Polyakova, N. V. (Запорожский национальный технический университет, 2013)
Представлен численно-полевой метод расчета переменной составляющей магнитного поля на поверхности вращающегося ротора турбогенератора. Он основан на многопозиционных расчетах магнитного поля с поворотами ротора и изменениями токов в обмотке статора. В фиксированных точках поверхности выделяется переменная составляющая магнитной индукции и для ее временной функции выполнен гармонический анализ. Разработанный метод универсален с точки зрения режимов возбуждения, конструкции и насыщения магнитопровода. Теоретические основы апробированы расчетными исследованиями в режимах холостого хода и короткого замыкания турбогенератора.

The method of calculating the alternating component of the magnetic field at the surface of the rotating rotor of a turbogenerator is presented. It is based on multiposition numerical calculations of the magnetic field with the turns of rotor and changes of currents in the stator winding. Discrete time functions of the alternating component of the magnetic induction are selected in points of the surface. For them, the harmonic analysis is conducted. The developed method is universal in terms of modes of excitation, designs and saturation of the magnetic core. The theory is confirmed by computational researches in the modes of no-load and short circuit of a large turbogenerator. In it, the alternating component of the magnetic induction on the rotor surface in the short-circuit mode is on an order of magnitude greater than in the no-load mode. Values and harmonic composition of the alternating component of the magnetic induction differ substantially at different points of the rotor surface. Harmonics are ponderable in the range from the level determined by the phase structure of stator winding to the level determined by the tooth structure of its core. The results obtained are qualitatively fit into the classical notion of oscillatory processes of the magnetic field on the rotor surface, but now the value and harmonic composition of the alternating component of the mag-netic induction are received adequate numerical filling. The result of work can be used for designing of a turbogenerators and other synchronous machines
Analysis of harmonic composition of the alternating magnetic field associated with the rotating rotor of a turbogenerator in the modes of no-load and short-circuits
Keywords: синхронные машины; короткое замыкание; численно-полевой расчет; колебательный процесс